CLINICAL AND RADIOLOGICAL FEATURES OF THE MAXILLARY SINUS IN PATIENTS AFTER REMOVAL OF FUNGAL BALL AND THEIR IMPACT ON THE FREQUENCY OF SUBANTRAL BONE AUGMENTATION COMPLICATIONS. - Ya.V. Shkorbotun (State Institution of Science «Research and Practical Center of Preventive and Clinical Medicine» State Administrative Department, 2021)
Abstract. The mucoperiostitis and local osteitis are radiological symptoms of the fungal ball of the maxillary sinuses. The condition of the mucoperiosteum and the adjacent bone in the alveolar bay of the maxillary sinus predict the results of dental implantation and subantral augmentation. The endoscopic access to the sinus by the antrostomy in the middle meatus and infraturbinal have been used to avoid excessive tissue injury during the removal of the fungal ball.